The Palm Pavilion enigma projects itself over Inhotim (Revista Apotheke, 2025)
A strangely building with modernist lines, one of many others scattered in the middle of a lush tropical garden, holds a repertoire of images, symbols and artifacts that at first glance seem meaningless. Together - architecture, landscape and other vestiges of a material culture whose only apparent cohesion is the diffuse presence of the palm tree - require visitors to carry out an investigative activity: to make sense of the signs that trigger their gaze and the landscape they see around them. Palm Pavilion (2006-2008), one of the main works by Rirkrit Tiravanija, based in Inhotim/Brumadinho-MG, allows us to question the critical and contesting role played by contemporary art in the face of current forms of spatial production. Concepts such as “exhibition protocol”, “cultural confinement” and “architectural frame” will be recovered in order to challenge the existing relationships between design, tropical landscape and cultural representation in one of the paradigmatic spaces of art and culture in contemporaneity.
Keywords: Rirkrit Tiravanija; Inhotim; contemporary art; contemporary spatialities; cultural representation